Measuring Distortions to Agricultural Incentives, Revisited - Anderson, Kym (2012)
Notwithstanding the tariffication component of the Uruguay Round Agreement on Agriculture, import tariffs on farm products continue to provide an incomplete indication of the extent to which agricultural producer and consumer incentives are distorted in national markets. As well, in developing countries especially, non-agricultural policies indirectly impact on agricultural and food markets. Empirical analysis aimed at monitoring distortions to agricultural incentives thus need to examine both agricultural and non-agricultural policy measures including import or export taxes, subsidies, and quantitative restrictions plus domestic taxes or subsidies on farm outputs or inputs and consumer subsidies for food staples. This paper addresses the practical methodological issues that need to be faced when attempting to undertake such a measurement task in developing countries. The approach is illustrated in two ways: by presenting estimates of nominal and relative rates of assistance to farmers in China for the period 1981-2005; and by summarizing estimates from an economy-wide CGE model of the effects on agricultural versus non-agricultural markets of the project's measured distortions globally as of 2004.